Effect of Blanching Time and Drying Method on Quality of Black Pepper (Piper nigrum) - Paul, Suchana; Ara, Rumman; Ahmad, Munshi Rashid; Hajong, Pradip; Paul, Gourango; Kobir, Md Shahriar; Rahman, Md Hafizur (Journal of Food Technology Research, 2021)
Quality of black pepper highly depends on pre-drying treatment and drying method. A pre-drying treatment, blanching (dipping in boiled water), is practiced in different countries. However, Bangladesh is yet to follow this technique to produce black pepper. So, this study investigated the effect of blanching, blanching time, and drying method on¬¬¬ black pepper quality. Pepper berries were treated in boiled water (blanched) for 1, 2, 3, 4, 5 minutes and kept fresh (untreated). Both treated and untreated pepper berries were dried under the open sun and in a mechanical dryer. Results showed that blanching time negatively correlated with drying duration for both mechanical and sun-drying method. Blanching limited the moisture content of dried pepper 5.33-11.52%, where the moisture content of untreated sun-dried black pepper was more than 12%. Mechanical dryer needed the lowest time over open sun-drying and decreased the moisture % to a safer level (<10%). The moderately blanched (1-3 min) black pepper was attracted by the consumers due to its uniform shiny black color. In contrast, untreated pepper could not meet the consumers' desire. Again, blanching for longer time deteriorated black peppers’ color and consequently decreased consumers' preference level to buy.